On the possibility of non-geodesic motion of massless spinning tops. (23rd June 2016) - Armaza, Cristóbal; Hojman, Sergio A; Koch, Benjamin; Zalaquett, Nicolás
Abstract: The motion of spinning massless particles in gravitationally curved backgrounds is revisited by considering new types of constraints. Those constraints guarantee zero mass ( P μ P μ = 0 ) and they allow for the possibility of trajectories which are not simply null geodesics. To exemplify this previously unknown possibility, the equations of motion are solved for radial motion in Schwarzschild background. It is found that the particle experiences a spin-induced energy shift, which is proportional to the Hawking temperature of the black hole background.